Introduction - Atalie, Gerhard (AmLit)
In this introduction, I will approach the special issue’s theme of positionality as informing critical reading approaches of North American literatures by and about minority subjects in a personal tone to match the required positionality statements in the essays. As an example, I will outline my own motivation for thematizing positionality after observing lived connections between my travels to Canada and the U.S. as well as becoming aware of how my family’s intergenerational experiences against the backdrop of transatlantic relations critically position myself. I will argue that reflections of one’s own positionality matter for researchers, while drawing from decolonial scholarship’s warningsagainst knowledge appropriation, extractivism, and a contemporary criticism of identity politics in an age of social protest. Instead, a responsibility towards the minority literatures that are being researched is posited in the essays included in this special issue from which self-reflexive statements are quoted in their original form. This special issue hopes to promote inclusive dialogues, beginning with self-positionings of global contributors within the field of North American Studies.